AUTOMATED ISOTOPIC MEASUREMENTS OF MICRON-SIZED DUST: APPLICATION TO METEORITIC PRESOLAR SILICON CARBIDE - Nittler L.R.; Alexander C.M.O.'D. (My University, 2003)
We report the development of a new analytical system allowing the fully automated measurement of isotopic ratios in micrometer-sized particles by secondary ion mass spectrometry (SIMS) in a Cameca ims-6f ion microprobe. Scanning ion images and image processing algorithms are used to locate individual particles dispersed on sample substrates. The primary ion beam is electrostatically deflected to and focused onto each particle in turn, followed by a peak-jumping isotopic measurement. Automatic measurements of terrestrial standards indicate similar analytical uncertainties to traditional manual particle analyses (e.g., ~3‰/amu for Si isotopic ratios). We also present an initial application of the measurement system to obtain Si and C isotopic ratios for ~3300 presolar SiC grains from the Murchison CM2 carbonaceous chondrite. Three rare presolar Si3N4 grains were also identified and analyzed. Most of the analyzed grains were extracted from the host meteorite using a new chemical dissolution procedure. The isotopic data are broadly consistent with previous observations of presolar SiC in the same size range (~0.5–4 μm). Members of the previously identified SiC AB, X, Y, and Z subgroups were identified, as was a highly unusual grain with an extreme 30Si enrichment, a modest 29Si enrichment, and isotopically light C. The stellar source responsible for this grain is likely to have been a supernova. Minor differences in isotopic distributions between the present work and prior data can be partially explained by terrestrial contamination and grain aggregation on sample mounts, though some of the differences are probably intrinsic to the samples. We use the large new SiC database to explore the relationships between three previously identified isotopic subgroups—mainstream, Y, and Z grains—all believed to originate in asymptotic giant branch stars. The isotopic data for Z grains suggest that their parent stars experienced strong CNO-cycle nucleosynthesis during the early asymptotic giant branch phase, consistent with either cool bottom processing in low-mass (M < 2.3M⊙) parent stars or hot-bottom burning in intermediate-mass stars (M > 4M⊙). The data provide evidence for a sharp threshold in metallicity, above which SiC grains form with much higher 12C/13C ratios than below. Above this threshold, the fraction of grains with relatively high 12C/13C decreases exponentially with increasing 29Si/28Si ratio. This result indicates a sharp increase in the maximum mass of SiC parent stars with decreasing metallicity, in contrast to expectations from Galactic chemical evolution theory.